Innovating to Be Competitive in the Marketplace Strengthening the fruits and vegetables value chain by implementing technologies and building technical, socio-organizational, and entrepreneurial capacity - Rivera Picado, Dagley María; Corrales Briceño, Ligia; Gutiérrez, Jaime (Catholic Relief Services, 2015)
This publication is the product of a participatory capitalization process facilitated by the International Center for Tropical Agriculture (CIAT) for the Program for Rural Enterprise Management, Health, and the Environment (PROGRESA). This document systematizes the experience gathered by PROGRESA’s contribution to the strengthening of the fruits and vegetables value chain, taking into account not only factors commonly included in agricultural development projects, such as the adoption of new technologies and technical assistance, but also mainstreaming components, such as organizational strengthening, market approach, and the development of partnerships, to produce a more innovative and comprehensive implementation proposal, focused on competitiveness.